The effect of behaviour change interventions on changes in physical activity and anthropometrics in ambulatory hospital settings: a systematic review and meta-analysis - Stephen Barrett; Stephen Begg; Paul O'Halloran; Owen Howlett; Jack Lawrence; Michael Kingsley (BMC, 2021)
Abstract Background The aim of this systematic review and meta-analysis was to investigate whether behaviour change interventions promote changes in physical activity and anthropometrics (body mass, body mass index and waist circumference) in ambulatory hospital populations. Methods Randomised controlled trials were collected from five bibliographic databases (MEDLINE, Embase, CINAHL, The Cochrane Central Register of Controlled Trials (CENTRAL) and PsycINFO). Meta-analyses were conducted using change scores from baseline to determine mean differences (MD), standardised mean differences (SMD) and 95% confidence intervals (95% CI). The Grades of Recommendation, Assessment, Development and Evaluation approach was used to evaluate the quality of the evidence. Results A total of 29 studies met the eligibility criteria and 21 were included in meta-analyses. Behaviour change interventions significantly increased physical activity (SMD: 1.30; 95% CI: 0.53 to 2.07, p < 0.01), and resulted in significant reductions in body mass (MD: -2.74; 95% CI: − 4.42 to − 1.07, p < 0.01), body mass index (MD: -0.99; 95% CI: − 1.48 to − 0.50, p < 0.01) and waist circumference (MD: -2.21; 95% CI: − 4.01 to − 0.42, p = 0.02). The GRADE assessment indicated that the evidence is very uncertain about the effect of behaviour change interventions on changes in physical activity and anthropometrics in ambulatory hospital patients. Conclusions Behaviour change interventions initiated in the ambulatory hospital setting significantly increased physical activity and significantly reduced body mass, body mass index and waist circumference. Increased clarity in interventions definitions and assessments of treatment fidelity are factors that need attention in future research. PROSPERO registration number: CRD42020172140.